Problematizing the Peace Discourse in World’s Largest Lesson: A Critical Exploration of Knowledge Production Through Discussions of Violence (In Factis Pax: Journal of Peace Education and Social Justice, 2020)
There is no single concept of peace in peace education. A large part of peace education recognizes and discusses different forms of violence and how they affect peace. Critical peace educators and transnational feminists recognize the need to critically consider concepts of violence. Using transnational feminist theory and a transnational feminist critical discourse analysis, this study problematizes the peace discourse that is created in peace educational material from World’s Largest Lesson. In order to problematize the overall peace discourse, this study critically explores the knowledge that is produced through discussions of different forms of violence. The peace education materials were selected based on their relevance topeace education occurring in relation to education for the Sustainable Development Goals. They were also selected based on their aim to produce knowledge specifically related to concepts of peace and violence. The study finds that overall,the  knowledge produced in the materials deemphasizes the interconnectedness of different forms of violence and, therefore, creates a peace discourse that is decontextualized, dehistoricized, depoliticized, and maintains the status quo. The study also discusses pedagogical implications in relation to Mohanty’s (2003) discussion of different pedagogical strategies. It is argued  that the peace discourse in World’s Largest Lesson contributes to a peace as tourist pedagogical model.